1998
DOI: 10.1523/jneurosci.18-09-03241.1998
|View full text |Cite
|
Sign up to set email alerts
|

Massive Mitochondrial Degeneration in Motor Neurons Triggers the Onset of Amyotrophic Lateral Sclerosis in Mice Expressing a Mutant SOD1

Abstract: Amyotrophic lateral sclerosis (ALS) involves motor neuron degeneration, skeletal muscle atrophy, paralysis, and death. Mutations in Cu,Zn superoxide dismutase (SOD1) are one cause of the disease. Mice transgenic for mutated SOD1 develop symptoms and pathology similar to those in human ALS. To understand the disease mechanism, we developed a simple behavioral assay for disease progression in mice. Using this assay, we defined four stages of the disease in mice expressing G93A mutant SOD1. By studying mice with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
450
0
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 638 publications
(478 citation statements)
references
References 20 publications
21
450
0
7
Order By: Relevance
“…Although there is no consensus about the exact role of mitochondrial abnormalities [61], it is accepted that mitochondrial dysfunction is an important hallmark of ALS pathogenesis [5,62,63]. Several authors have shown deficits in mitochondrial function in the spinal cord and muscles of both human patients [64] and animal models of ALS [65][66][67]. Resveratrol improves mitochondrial function and induces biogenesis, although there is some controversy about whether this effect is mediated by AMPK activation [18] or by Sirt1 [16,68].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus about the exact role of mitochondrial abnormalities [61], it is accepted that mitochondrial dysfunction is an important hallmark of ALS pathogenesis [5,62,63]. Several authors have shown deficits in mitochondrial function in the spinal cord and muscles of both human patients [64] and animal models of ALS [65][66][67]. Resveratrol improves mitochondrial function and induces biogenesis, although there is some controversy about whether this effect is mediated by AMPK activation [18] or by Sirt1 [16,68].…”
Section: Discussionmentioning
confidence: 99%
“…For example, several lines of evidence indicate that excessive stimulation of glutamate receptors, perhaps due to impairment to the glutamate-transport system and, in particular, of the astroglial transporter EAAT2, could lead to Ca 2þ overload in mitochondria, resulting in overproduction of ROS and oxidative stress-mediated motor-neuron damage. In addition, motor neurons could become more sensitive to glutamate-mediated excitotoxicity in the presence of mutant SOD1 in mitochondria (76).…”
Section: Discussionmentioning
confidence: 99%
“…In mice with the ALSlinked G37R SOD1 mutation, the presence in axons and dendrites of membrane-bound vacuoles, which seem to be derived from degenerating mitochondria (5), is noteworthy. Massive mitochondrial degeneration is also observed in motor neurons of G93A SOD1 mutant mice at the onset of the disease (8), when electron transfer chain activity and ATP synthesis appear severely injured (9). Furthermore, a selective decrease in the activity of cytochrome c oxidase, encoded by the mitochondrial genome, occurs in motor neurons of sporadic ALS patients (10), and the reduction in the amount of mitochondrial DNA in the spinal cord of ALS patients correlates with a decrease in the activities of citrate synthase and the respiratory chain complexes IϩIII, IIϩIII, and IV (11).…”
mentioning
confidence: 97%